Using human induced pluripotent stem cells (hiPSCs) to investigate the mechanisms by which Apolipoprotein E (APOE) contributes to Alzheimer’s disease (AD) risk - Sreedevi Raman; Nicholas Brookhouser; David A. Brafman (Neurobiology of Disease, 2020)
Although the biochemical and pathological hallmarks of Alzheimer’s disease (AD), such as axonal transport defects, synaptic loss, and selective neuronal death, are well characterized, the underlying mechanisms that cause AD are largely unknown, thereby making it difficult to design effective therapeutic interventions. Genome-wide association studies (GWAS) studies have identified several factors associated with increased AD risk. Of these genetic factors, polymorphisms in the Apolipoprotein E (APOE) gene are the strongest and most prevalent. While it has been established that the ApoE protein modulates the formation of amyloid plaques and neurofibrillary tangles, the precise molecular mechanisms by which various ApoE isoforms enhance or mitigate AD onset and progression in aging adults are yet to be elucidated. Advances in cellular reprogramming to generate disease-in-a-dish models now provide a simplified and accessible system that complements animal and primary cell models to study ApoE in the context of AD. In this review, we will describe the use and manipulation of human induced pluripotent stem cells (hiPSCs) in dissecting the interaction between ApoE and AD. First, we will provide an overview of the proposed roles that ApoE plays in modulating pathophysiology of AD. Next, we will summarize the recent studies that have employed hiPSCs to model familial and sporadic AD. Lastly, we will speculate on how current advances in genome editing technologies and organoid culture systems can be used to improve hiPSC-based tools to investigate ApoE-dependent modulation of AD onset and progression.